2007
DOI: 10.1007/s00192-007-0486-6
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal cystocele repair with polypropylene mesh using a tension-free technique

Abstract: This study describes an original surgical technique for the correction of medium/high-degree cystocele using a tension-free way to apply a polypropylene mesh: the "tension-free cystocele repair" (TCR). About 218 patients were available with a mean follow-up of 38 months. This technique showed an elevated rate of anatomic correction (75.7%), a statistically significant correction of storage symptoms (48.6 vs 32.5%, p < 0.05), voiding symptoms (40.3 vs 8.3%, p < 0.05), and symptoms associated with pelvic organ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
0
13
0
10
Order By: Relevance
“…The technique for cystocele repair adopted in this study was TCR, described by our group in a previous report [15]. As a result, the outcome reported in the present study might not be predictive of the effect of the studied grafts when other surgical techniques, such as the popular transobturator approach, are adopted.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The technique for cystocele repair adopted in this study was TCR, described by our group in a previous report [15]. As a result, the outcome reported in the present study might not be predictive of the effect of the studied grafts when other surgical techniques, such as the popular transobturator approach, are adopted.…”
Section: Discussionmentioning
confidence: 49%
“…All patients underwent tension-free cystocele repair (TCR) [15] and levator myorrhaphy (LM). Concomitant hysterectomy was performed on 26 patients (27.6%) in the Pelvicol® group and 13 patients (13.5%) in the Gynemesh PS® group.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using vaginal polypropylene implants for cystocele repair generally report favorable mid-term (up to 37 months of mean follow-up) anatomic outcomes, i.e., anatomical correction of the cystocele (stage 0 or 1) between 64% and 100% [3][4][5][17][18][19][20][21][22][23][24][25][26][27][28][29]. Only three studies have reported anatomical success rates lower than 85%, after real free [28] or retropubic free techniques [22,23]. On the three randomized controlled trials which have shown significant better anatomical outcomes using polypropylene implant, one used a free technique [3] and two a transobturator technique [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Cervigni et al [16] ont un taux de récurrence de 24,3 % à 38 mois de suivi avec une prothèse de polypropylène et 5 % de réintervention. Trois études prospectives ont comparé la colporraphie antérieure et l'utilisation de prothèse synthétique par voie vaginale.…”
Section: Discussionunclassified